International Management: Culture and Beyond - Richard Mead; Tim G. Andrews (England John Wiley & Sons, Ltd, 2009)
As in previous editions of this popular text on cross-cultural management, students will find here an invaluable guide to key management theories, linked to practical examples from all round the world. The book's key distinctive feature remains its truly international profile, with current examples from the US, Europe, Asia and new perspectives in this edition from other regions. Discussion of cross-cultural models is updated by including the 'crossvergence' framework developed during the 1990s, as well as the latest new research on organizational culture Coverage of how and to what extent cultural variation affects the implementation of e-technology at the workplace (esp. in multinational subsidiaries) New material on the management of marketing/sales teams across borders and implications of cultural differences for expatriate managers. The addition of several new cases, from the Middle East, Latin America and Africa as well as new cases in in Asia. The 4th edition retains the special appendix on how to write a successful dissertaion or project which makes this a useful text for both MBA and advanced undergraduate courses.
Keywords: International business enterprises; Management; Corporate culture; Intercultural communication; Textbooks; International Business and Management (ECO2023-N )